A Cross-Cultural Understanding of Depression Among Abused Women. (October 2016) - Wong, Janet Y. H.; Tiwari, Agnes; Fong, Daniel Y. T.; Bullock, Linda
Little research has addressed depression in abused women across cultures. This review examines depression and intimate partner violence (IPV) by comparing and contrasting the IPV definitions, family dynamics, coping, and expressions of depression of women in China, Japan, India, and the United States. Findings reveal that depression is expressed differently across cultures. Somatization is commonly found in Asian countries, but it is not properly assessed by existing Westernized depression assessment tools. In addition, cultural factors were shown to shape abused women's ways of adaptive coping. Cultural awareness and sensitivity are fundamental for successful assessment and intervention for abused women with depression.